The Controversy of Environmental Law Policies from Regulation Perspective - Triono Eddy (UNISSULA, 2023)
Government Regulation in Lieu of Act No. 2 of 2022 was born as a result of obstacles in the investment sector, not due to the issue of climate change as contained in the Job Creation Government Regulation. The purpose of the research was to find out and analyze because the issuance of PERPPU Job Creation ignores the Constitutional Court Decision Number 91/PUU-XVIII/2020, which is related to Article 22 of the 1945 Constitution concerning the urgency which imposes benchmarks according to circumstances and is necessary to prevent a legal vaccum. The method used is normative research which studies legal norms and literature. Government Regulations in Lieu of Laws become the full authority of the President in accordance with the constitution and are regulated in Article 22 Paragraph 1 of the 1945 Constitution. In this Government Regulation in lieu of the Job Creation Law there are articles that have problems with the environment. The article will regulate issues of environmental permits, the role of the community in the AMDAL (Environmental Impact Analysis), use of forest areas and criminal sanctions.